Wychowanie przedszkolne w czasach pandemii – wyzwanie dla diady nauczyciel–rodzic - Katarzyna Ziębakowska-Cecot (Edukacja Ustawiczna Dorosłych)
The need for evolution in preschool and early childhood education has been announced in Poland for years. However, it was only the outbreak of the COVID-19 pandemic that proved Polish schools must and can change. Consideration should be given to the individualization of education, constructivist approach, formative assessment, use of ICT, and supporting pupils’ independence. Despite the challenges and initial setbacks, it is worth drawing conclusions from distance learning. According to the students of UTH in Radom – future teachers of elementary education – the positive aspects of the pandemic include growth in digital competences, development of cooperation between educators and parents (as well as development of the strategies to support pre-schoolers’ families), use of traditional media, and increased creativity of teachers.